The social demographic, social economic characteristics and health status of lactating mothers in Mwanamukia. A Case of Nairobi Metropolis - Nkirigacha, Dr. Evayline Muthoni (International Journal of Scientific Research and Management (IJSRM), 2019)
Socio-economic status is a multi-factorial condition which is embedded in environmental, material and personal characteristics. The aim of this study was to determine the social demographic and social economic characteristics of lactating mothers in Mwanamukia, Nairobi and their health condition. This cross sectional study was conducted on 260 purposively selected lactating women living in Mwanamukia, Nairobi Kenya. A structured, validated and pre-tested questionnaire was used to obtain information on social, economic and demographic characteristics and the health staus. Data was entered into SPSS version 20 and analyzed using descriptive statistics and Pearson correlation coefficient was used to determine associations. Majority of the respondents were married (62.7%) or single (25.4%). 44.4% had achieved primary school education while 40% had attained Secondary ‘O’ level education. The maximum number of people living in households was 12 while the average number was 6. The study had respondents from different ethnic backgrounds. Majority Meru (25.5%) and Luhya (17.3%).  The average monthly income was 27, 154.12 Kenyan shillings. Majority were business people (28.6%) and housewives (23.9%). 71.5% of household heads were men while 28.5% were women. Majority 73.5% suffered from fever, worm infestation 12.1%, Diarrhea 2.2%, diabetes 2.1% and HIV/AIDS 2.1More than half of the respondents interviewed were literate, married and lived in households headed by men.  A quarter of them were business people, single and had Meru ethnicity. The highest number of people fell in the 36-40 years age category. More than half of the respondents had a given form of health condition.